2018
DOI: 10.1002/ejp.1283
|View full text |Cite
|
Sign up to set email alerts
|

Nondental orofacial pain in dental practices – diagnosis, therapy and self‐assessment of German dentists and dental students

Abstract: Interdisciplinary pain treatment seems to be well acknowledged, however, with a focus on referral within the community of dental specialists. Dental curricula and post-graduate trainings need to implement the diagnosis and treatment options of non-dental orofacial pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 21 publications
(25 reference statements)
1
40
0
2
Order By: Relevance
“…When comparing the consensus among OFP specialists, Swedish specialists had a higher consensus than Saudi specialists for both the "treatment and prognosis" and "etiology" domains. These differences might suggest that there is a need to improve healthcare workers' knowledge in TMD in Saudi Arabia by improving not only medical professional training but also by embracing specialized institutes with interdisciplinary management approaches [2]. In Sweden, OFP has been recognized as a specialty since 1993 by the Swedish National Board of Health and Welfare, which fosters the current suggestion.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…When comparing the consensus among OFP specialists, Swedish specialists had a higher consensus than Saudi specialists for both the "treatment and prognosis" and "etiology" domains. These differences might suggest that there is a need to improve healthcare workers' knowledge in TMD in Saudi Arabia by improving not only medical professional training but also by embracing specialized institutes with interdisciplinary management approaches [2]. In Sweden, OFP has been recognized as a specialty since 1993 by the Swedish National Board of Health and Welfare, which fosters the current suggestion.…”
Section: Discussionmentioning
confidence: 85%
“…Despite the fact that temporomandibular disorders (TMD) are a common musculoskeletal disease affecting the temporomandibular joint and associated structures in the orofacial region [1], many dentists are unable to treat patients suffering from TMD. Until recently, general dentists often misdiagnosed the orofacial pain (OFP) of the temporomandibular joint (TMJ) with OFP associated with the dentoalveolar region, which results in incorrect management [2]. Many studies found that general dentists spent additional time and effort with patients suffering from TMD [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziegeler et al found that 83% of German senior dental students reported that OFP was only included in a lecture on another topic (13). Thirty percent of senior German dental students did not feel confident at all in diagnosing OFP, while 48% were somewhat confident.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and treatment of dental pain is one of the everyday and nevertheless most important tasks of both dentists and dental students [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%